Acceptability of identification and management of perinatal anxiety: a qualitative interview study with postnatal women - Meades, Rose; Moran, Patricia M.; Hutton, Una; Khan, Rafiyah; Maxwell, Margaret; Cheyne, Helen; Delicate, Amy; Shakespeare, Judy; Hollins, Kathryn; Pisavadia, Kalpa; Doungsong, Kodchawan (Pim); Edwards, Rhiannon Tudor; et al. (Frontiers in Public Health, 2024)
Background Anxiety in pregnancy and postpartum is highly prevalent but under-recognized and few women receive adequate support or treatment. Identification and management of perinatal anxiety must be acceptable to women in the perinatal period to ensure that women receive appropriate care when needed. We aimed to understand the acceptability to women of how anxiety was identified and managed by healthcare professionals. Method We conducted in-depth qualitative interviews with 60 women across England and Scotland approximately 10 months after birth. Women were sampled from an existing systematically recruited cohort of 2,243 women who recorded mental health throughout pregnancy and after birth. All women met criteria for further assessment of their mental health by a healthcare professional. We analyzed the data using a theoretical framework of acceptability of healthcare interventions. Results Interview data fitted the seven constructs within the theoretical framework of acceptability. Women valued support before professional treatment but were poorly informed about available services. Services which treated women as individuals, which were accessible and in which there was continuity of healthcare professional were endorsed. Experience of poor maternity services increased anxiety and seeing multiple midwives dissuaded women from engaging in conversations about mental health. Having a trusted relationship with a healthcare professional facilitated conversation about and disclosure of mental health problems. Conclusion Women’s experiences would be improved if given the opportunity to form a trusting relationship with a healthcare provider. Interventions offering support before professional treatment may be valued and suitable for some women. Clear information about support services and treatment options available for perinatal mental health problems should be given. Physiological aspects of maternity care impacts women’s mental health and trust in services needs to be restored. Findings can be used to inform clinical guidelines and research on acceptable perinatal care pathways in pregnancy and after birth and future research.